Kontribusi Ibu Rumah Tangga Pedagang Siri Dalam Membantu Pendapatan Keluarga Di Kecamatan Laubaleng Kabupaten Karo - Nurlela Ginting; TM Jamil; Nana Suraiya (Universitas Syiah Kuala, 2019)
This study raised the question 1) how much revenue is given to the family? 2) how much capital is required to trade betel? 3) what factors are causing housewives to trade betel? This study aims to determine the contribution of revenue given to the family, to determine the amount of capital required housewife betel traders in the increase family income, to determine the factors that cause a housewife trade betel. The approach used in this study is a qualitative approach with descriptive method. The subjects were housewives betel traders in District Laubaleng Karo many as 20 people, the object of this study is the income housewives betel merchant. The data collection was done by using library research, observation and interviews. Data were analyzed by using the formula Average (x ) and the formula for the percentage (%). The results showed that the contribution made by the housewife to her family betel trader is 81.9%. Factors that lead housewife betel trade because their husbands were minimal, wants to replace her husband make a living, want to have their own income. The capital required highest respondent is Rp 1,000,000, and the lowest is Rp 200,000 per day.